Effective Implementation of Outcome-based Education: The Role of Faculty Awareness - Srinivasa Pai P; Gururaj Upadhyaya (Indonesian Journal Of Educational Research and Review, 2021)
Accreditation of technical institutions is very important to guarantee the quality of technical education that is being offered. Outcome based education (OBE) is followed in the delivery of technical education across all Institutions in India and the National Board of Accreditation (NBA), which is the nodal accreditation body for technical institutions in India follows outcome based accreditation (OBA) in the accreditation of technical programs. In the OBE and OBA, faculty constitutes the most important component and plays an important role in facilitation of the same. In this regard, the authors felt that there is a need to understand the level of awareness of faculty about the same and accordingly a survey was conducted among the faculty of the authors’ institution, which is an autonomous Institution and comes under Tier I scheme of NBA accreditation process. From among 285 faculty members, about 96 participated in the survey. This paper discusses the significance of faculty’s awareness and involvement in the accreditation process and implementation of OBE. The results of the survey indicate some interesting findings, which is discussed in detail. Some suggestions and guidelines are given at the end to increase the level of awareness and their involvement in the OBE and OBA processes respectively.